ANALYSIS OF THE QUALITY OF PUBLIC SERVICES IN DEATH BENEFIT PROGRAMS IN MAGELANG CITY - Lailia Kasanah; Suci Iriani Sinuraya; Eny Boedi Orbawati (Journal of Social Politics and Governance (JSPG), 2025)
The Death Benefit Program (Santunan Kematian/Sankem) is a social assistance initiative by the Magelang City Government, providing financial aid to the heirs or designated family members of deceased individuals to alleviate funeral costs and related expenses. Eligibility requires beneficiaries to be native residents of Magelang City and listed as poor households in the Integrated Social Welfare Data (DTKS). This study analyzes and evaluates the quality of public service in the Death Benefit Program, employing a qualitative case study approach. Findings reveal suboptimal service quality, with several dimensions failing to meet established standards: 1) Tangibles: Inadequate facilities and infrastructure, coupled with complex administrative requirements, hinder accessibility. 2) Reliability: The absence of a Standard Operating Procedure (SOP) for service delivery. 3) Responsiveness: While officials promptly record benefit applications, fund disbursement faces significant delays, reducing the program’s effectiveness. 4) Assurance: No guaranteed timeline for disbursement, leading to frequent delays. To address these issues, the study recommends: Improving facilities and streamlining administrative processes, formalizing an SOP to standardize service delivery, implementing a parallel disbursement system to expedite fund distribution, and enhancing complaint resolution mechanisms to ensure accountability. These measures aim to optimize service quality, ensuring the program fulfills its objective of social risk mitigation.